Clinical characteristics of the Ala21Val variant in the myelin proteolipid protein 1 (PLP1) gene associated with Pelizaeus-Merzbacher disease in a Brazilian male patient - Pedro Manzke; Pedro Renato P. Brandão; Talita Balieiro; Diógenes Diego de Carvalho Bispo; Maria Joana Osório; Gustavo Barcelos Barra (Human Genome Variation)
Abstract Here, we report the case of a 29-year-old male with classic Pelizaeus-Merzbacher disease (PMD) harboring the PLP1 variant NM_000533.5:c.62 C > T, leading to an NP_000524.3:p.(Ala21Val) alteration in the first transmembrane domain of the protein. He presented with developmental delays, nystagmus, spastic paraparesis, optic atrophy, dysphagia, appendicular ataxia, and progressive head tremor. Brain MRI revealed hypomyelination, diffuse white matter hyperintensity, and atrophy of the corpus callosum and cerebellum, expanding the known clinical spectrum of PMD.